END-OF-LIFE CARE FOR PEOPLE WITH DEMENTIA. Issue 2 (1st June 2013) - Cartwright, C
Abstract : Introduction: A Diagnosis of Dementia—what does this mean? Receiving a diagnosis of dementia raises many challenges for the person themselves and for their carers and other family members and friends. However, it can also provide opportunities, to plan ahead, to put financial and other affairs in order and, for those who are in the early stages of dementia, to travel or do other things with family and friends. This session will consider some of the issues that need to be addressed at this time. These include: when does a person have capacity to make their own decisions?; the need to undertake Advance Care Planning to appoint a substitute decision-maker and write an Advance Directive; the legally available options that the person may want to include in their Advance Care Plans; an understanding of palliative care; their right to adequate pain relief in terminal illness (and the related issue of what is/is not euthanasia). Issues for Carers of people with dementia will also be covered. Finally, as there is increasing activity in Australia to introduce euthanasia legislation, the special concerns for people with dementia, should such legislation be introduced, will be discussed.